Thermospheric parameters long‐term variations retrieved from ionospheric observations in Europe. Issue 11 (28th November 2016) - Mikhailov, A. V.; Perrone, L.
Abstract: Recently developed method to retrieve thermospheric parameters ( T ex, O, O2, and N2 ) and the total solar EUV flux with λ < 1050 Å from routine fo F 1 ionosonde observations has been applied to monthly median fo F 1 data on Rome, Slough/Chilton, and Juliusruh stations to analyze long‐term trends in the thermospheric parameters. For the first time exospheric temperature and neutral composition were obtained for June noontime conditions over the period of 5 solar cycles. The retrieved parameter manifested solar cycle and long‐term (some solar cycles) variations with a rising phase in 1965–1985 and falling phase in 1985–2008. The retrieved thermospheric parameters were shown to be close to the MSIS‐86 model ones exhibiting very small (<1% per decade) and statistically insignificant linear trends estimated either over all 56 years or only over the years of solar minimum. No peculiarities in long‐term variations in relation with the last deep solar minimum have been revealed. The source of the thermospheric parameter long‐term trends is the Sun, i.e., they have a natural (not anthropogenic) origin and are mainly controlled by long‐term variations of solar and geomagnetic activity. Key Points: To retrieve neutral composition, temperature, and the total solar EUV flux at three ionosonde stations To estimate thermospheric parameter long‐term trends To compare the obtained trends with the published thermospheric trend estimates